1999
DOI: 10.1152/ajpgi.1999.276.4.g965
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol modulation of intestinal epithelial tight junction barrier

Abstract: Previous studies have shown that high concentrations of ethanol (≥40%) cause functional damage of the gastrointestinal epithelial barrier by direct cytotoxic effect on the epithelial cells. The effects of lower noncytotoxic doses of ethanol on epithelial barrier function are unknown. A major function of gastrointestinal epithelial cells is to provide a barrier against the hostile substances in the gastrointestinal lumen. The apicolaterally located tight junctions (TJs) form a paracellular seal between the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
211
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(238 citation statements)
references
References 25 publications
25
211
0
2
Order By: Relevance
“…However, ethanol up to 5% concentration failed to increase paracellular permeability, suggesting that ethanol metabolism to acetaldehyde is required for the action. This was confirmed by another study where ethanol up to 3% showed no significant effect on paracellular permeability in Caco-2 cell monolayers (Ma et al, 1999). This study showed that ethanol increased paracellular permeability at 7.5% concentration.…”
Section: Role Of Acetaldehyde In Increasing Intestinal Permeabilitysupporting
confidence: 75%
“…However, ethanol up to 5% concentration failed to increase paracellular permeability, suggesting that ethanol metabolism to acetaldehyde is required for the action. This was confirmed by another study where ethanol up to 3% showed no significant effect on paracellular permeability in Caco-2 cell monolayers (Ma et al, 1999). This study showed that ethanol increased paracellular permeability at 7.5% concentration.…”
Section: Role Of Acetaldehyde In Increasing Intestinal Permeabilitysupporting
confidence: 75%
“…The possibility of a toxic effect of ethanol on the small-bowel epithelium has been described in healthy subjects (34,39) and in in vitro studies (40)(41)(42)(43). However, patients from both groups consumed the same amount of alcohol, which lessens the implication that ethanol itself is involved in permeability disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…These include epithelial apoptosis, mucosal ulceration, and altered tight junction protein expression. 1,12,[22][23][24][25][26][27] While apoptosis and ulceration can certainly disrupt the mucosal barrier, abundant experimental evidence suggests that these alone cannot explain the barrier dysfunction observed. 23 One pair of recent reports has shown that increased expression of the tight junction protein claudin-2 can contribute to the reduced barrier function seen in response to IL-13, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the documented role of MLCK in regulating epithelial tight junction permeability in response to physiological and pathophysiological stimuli in both in vitro and in vivo models. 13,15,19,27 The mechanism by which TNF induces epithelial MLCK activation is not well understood, 12 but studies in cultured epithelial monolayers suggest a role for TNF-dependent transcriptional activation of MLCK. 16,17 As a result, both MLCK expression and activity are increased, as demonstrated by increased MLC phosphorylation.…”
Section: Discussionmentioning
confidence: 99%